Aldosterone synthase gene is not a major susceptibility gene for progression of chronic kidney disease in patients with autosomal dominant polycystic kidney disease - Gnanasambandan Ramanathan; Ramprasad Elumalai; Soundararajan Periyasamy; Bhaskar V. K. S. Lakkakula (Saudi Journal of Kidney Diseases and Transplantation, 2017)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common heritable kidney disease and is characterized by bilateral renal cysts. Hypertension is a frequent cause of chronic kidney disease (CKD) and mortality in patients with ADPKD. The aldosterone synthase gene polymorphisms of the renin-angiotensin-aldosterone system have been extensively studied as hypertension candidate genes. The present study is aimed to investigate the potential modifier effect of CYP11B2 gene on the progression of CKD in ADPKD. One hundred and two ADPKD patients and 106 healthy controls were recruited based on Ravine inclusion and exclusion criteria. The three tag-SNPs within CYP11B2 gene (rs3802230, rs4543, and rs4544) were genotyped using FRET-based KASPar method. Cochran-Armitage trend test was used to assess the potential associations between these polymorphisms and CKD stages. Mantel- Haenszel stratified analysis was used to explore confounding and interaction effects of these polymorphisms. Of the three tag-SNPs genotyped, rs4544 polymorphism was monomorphic and rs3802230 deviated Hardy-Weinberg equilibrium. The CYP11B2 tag-SNPs did not show significant association with ADPKD or CKD. Further, these polymorphisms did not exhibit confounding effect on the relationship between CKD progression and hypertension. Our results suggest that aldosterone synthase gene is not a major susceptibility gene for progression of CKD in South Indian ADPKD patients.